The development of landscapes of investigation in the in-service primary teacher education - Afini, Dais Capucho; da Silva, Guilherme Henrique Gomes [UNESP] (FapUNIFESP (SciELO), 2024)
Landscapes of investigation are learning environments where it is possible to develop pedagogical tasks with openness to dialogue and which invite students to engage in investigative practices in mathematics classes. In this research, we sought to understand how primary school teachers, engaged in an in-service education practice, implement pedagogical work with landscapes of investigation. Using a qualitative research approach, the Case Study methodology, and participant observation as a method, data were produced from a continuing education practice involving 11 teachers working in the early years of elementary education of schools from a city in southern Minas Gerais. Data production instruments included field notes, audio recordings, records made by teachers in the follow-up notebook, and in the final evaluation activity. For data organization and analysis, we used a thematic construction proposal. In this article, we discuss one of the constructed themes, whose results indicate the importance of teachers experiencing landscapes of investigation during in-service education practice, producing their own pedagogical material in this process, and the need to discuss the mathematical content involved in the proposed tasks. Furthermore, the results point out factors that influence teachers' acceptance of the invitation to engage in formative practices focused on landscapes of investigation, which have different characteristics from students' acceptance.
O desenvolvimento de cenários para investigação na formação continuada de professores dos anos iniciais do Ensino Fundamental
Keywords: Critical Mathematics Education; Investigative-tasks; Landscapes of investigation; Primary schools; Teacher education